2019
DOI: 10.1080/14778238.2019.1701964
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial ecosystems: analysing the status quo

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 44 publications
(33 reference statements)
0
39
0
1
Order By: Relevance
“…If two or more authors are jointly cited in another publication, the cited authors form a co-citation relationship. Thus, co-citation analysis enables the identification of the research themes that are attracting attention by citing authors (McCain, 1990;Kang et al, 2019;Zhao and Strotmann, 2015).…”
Section: Bibliometric Methods and Data Collectionmentioning
confidence: 99%
“…If two or more authors are jointly cited in another publication, the cited authors form a co-citation relationship. Thus, co-citation analysis enables the identification of the research themes that are attracting attention by citing authors (McCain, 1990;Kang et al, 2019;Zhao and Strotmann, 2015).…”
Section: Bibliometric Methods and Data Collectionmentioning
confidence: 99%
“…Concepts of EE supplement entrepreneurship research by providing a systemic framework for established theories (Ferreira et al 2019). Despite the pending consolidation in terms of definitions and frameworks (Kang et al 2019;Spigel and Harrison 2018;Stam 2015), two major research streams can be distinguished in the literature. The first stream provides an actor-centric view of entrepreneurship (Stam 2015), which focuses on social systems, configurations, and networks as a focal point of entrepreneurship (Theodoraki et al 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Previous research showed that entrepreneurial activity is strongly influenced by the spatial context (Korsgaard et al 2015). Recent EE research underlined the need for a better understanding of how entrepreneurs' environment affects their entrepreneurial activities (Kang et al 2019;Stam 2015). Among existing work of EE (for examples of EE frameworks see Harrison 2018 andStam 2015), the regional EE model of de Villiers Scheepers et al (2018) highlights three subsystems, which enable value creation in a regional EE.…”
Section: Regional Entrepreneurial Ecosystemsmentioning
confidence: 99%
“…However, research on behaviors, inter-dependencies and relational governance in entrepreneurial ecosystems remains substantially underdeveloped and represents a crucial barrier to understanding when and why ecosystems flourish or flounder. (Aarikka-Stenroos and Ritala 2017; Kang et al 2019;Scott et al 2019;Spigel 2017). We attempt to address this critical oversight and contribute to a network-based view of entrepreneurial ecosystems (Spigel 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Within this stream, authors focus their efforts on the factors that influence access to and use of interactions within complex and broader social environments. While promising results have emerged, this body of work is still in its infancy (Mueller and Jungwirth 2016;Kang et al 2019). Central to this research is the emerging pattern among descriptive accounts of the dependency the entrepreneurial ecosystems have on local conditions (Cavalo et al 2018).…”
Section: Introductionmentioning
confidence: 99%